Impact of the Cd2+ treatment on the electrical properties of Cu2ZnSnSe4 and Cu(In, Ga)Se2 solar cells. (28th February 2015) - Ben Messaoud, Khaled; Buffière, Marie; Brammertz, Guy; ElAnzeery, Hossam; Oueslati, Souhaib; Hamon, Jonathan; Kniknie, Bas J.; Meuris, Marc; Amlouk, Mosbah; Poortmans, Jef
Abstract: The present contribution aims at determining the impact of modifying the properties of the absorber/buffer layer interface on the electrical performance of Cu2 ZnSnSe4 (CZTSe) thin‐film solar cells, by using a Cd 2+ partial electrolyte (Cd PE) treatment of the absorber before the buffer layer deposition. In this work, CZTSe/CdS solar cells with and without Cd PE treatment were compared with their respective Cu(In, Ga)Se2 (CIGSe)/CdS references. The Cd PE treatment was performed in a chemical bath for 7 min at 70 °C using a basic solution of cadmium acetate. X‐ray photoemission spectroscopy measurements have revealed the presence of Cd at the absorber surface after the treatment. The solar cells were characterized using current density–voltage (J–V), external quantum efficiency, and drive‐level capacitance profiling measurements. For the CZTSe‐based devices, the fill factor increased from 57.7% to 64.0% when using the Cd PE treatment, leading to the improvement of the efficiency (η) from 8.3% to 9.0% for the best solar cells. Similar observations were made on the CIGSe solar cell reference. This effect comes from a considerable reduction of the series resistance (RS ) of the dark and light J–V, as determined using the one‐diode model. The crossover effect between dark and light J–V curves is also significantly reduced by Cd PE treatment. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Modification of the absorber surface properties by Cd 2+ treatment (Cd 2+ partial electrolyte) results in the following: formation of Cd(OH)2 on the absorber surface, deposition of thinner chemical bath‐deposited CdS buffer layer, and a smaller space charge region. The impact on electrical performances is as follows: decrease of the series resistance (RS ), increase of the fill factor, increase of the efficiency (η), and reduction of the crossover between the dark and light current density–voltage curves.